(untitled) (Stamford Journal of Pharmaceutical Sciences, 2011)
A reverse phase high performance liquid chromatographic (RP-HPLC) method has been developed for the simultaneous estimation of Amlodipine Besylate and Hydrochlorothiazide in combine dosage form. Amlodipine Besylate (AML) is a long acting calcium channel blocker and in the treatment of CVS disorder. Hydrochlorothiazide (HCT) is a diuretic and antihypertensive. The mobile phase used was a combination of Water: Methanol (70:30). The detection of the combined dosage form was carried out at 245nm and a flow rate employd was 0.5ml/min. The retention time for Amlodipine Besylate and Hydrochlorothiazide was found to be 6.95 and 2.65 min respectively. Linearity was obtained in the concentration range of 6 to 18μg/ml of Amlodipine Besylate and 6 to 18μg/ml of Hydrochlorothiazide with a correlation coefficient of 0.997 and 0.9974. Detector consists of photodiode array detector; the reversed phase column used was RP-C18 (5 μm size, 250mm, 4.6mm i.d.) at ambient temperature. The developed method was validated according to ICH guidelines and values of accuracy, precision and other statistical analysis were found to be in good accordance with the prescribed values. Thus the proposed method is precise, selective and rapid for simultaneous estimation of Amlodipine Besylate and Hydrochlorothiazide in routine analysis. Key Words: Simultaneous Estimation; Amlodipine Besylate; Hydrochlorothiazide; HPLC. DOI: 10.3329/sjps.v3i1.6798 S. J. Pharm. Sci. 3(1): 49-53